Implementation of scouting techniques material on first aid for accidents in scouts of Gudep Bumi Bahari - Muh. Khaerul Ummah BK; H. Hamna; Karmila Risa Rahmawati; Syaiful Hidayat; Ananda Amelia (Journal of Community Service and Empowerment, 2024)
Scouting is one of the activities of forming discipline, morals, character, and mental development with a learning process outside the school environment and outside the family environment which is packaged in an interesting and fun way carried out in the open air. There are two kinds of scout learning material, namely knowledge learning and scouting techniques. In scouting activities there are several scouting techniques that are often used for example camping, exploration, terrain orientation, and mountain climbing. Therefore, it is necessary to implement the scouting technique of scout first aid material for scouts through a Community Service program that is integrated with lecture activities at the project location to implement the scouting technique of scout first aid material for scouts in Gudep Bumi Bahari so that scouts in Gudep Bumi Bahari can know and apply every step in performing first aid in accidents during scouting activities.  The purpose of this service is to increase the knowledge and skills of the first aid of the Cub Scouts, because the knowledge of first aid in the accident of the Cub Scouts of Gudep Bumi Bahari is still lacking.   The method used in this community service is lecture-based coaching, practice and educational games, interviews are conducted as a final evaluation. The service program carried out with the project implementation team can be carried out according to targets such as increasing the understanding and skills of Scouts related to first aid material at Gudep Bumi Bumi Bahari in SD Negeri Pulias Abaling.